A study on factors influencing social media among Keningau Vocational College's staffs / Siti Zalifah Sajimin @ Wagimin - Sajimin @ Wagimin, Siti Zalifah (2015)
Nowadays, social media has become an important and very popular tool for communication Understanding factors that influence the adoption of use of social media services can assist marketers in selecting the social media to use and how to best structure their social media content. This research examined factors impacting the adoption of use of various social media services - Facebook, E-mail, Whatsapp/Wechat/Telegram - among Keningau Vocational College staffs in different level management; Top management, Middle management and Low management. The findings included the positive relationship between demographic profile, usefulness and safe.